Activation of the mitochondrial permeability transition pore modulates Ca(2+) responses to physiological stimuli in adult neurons - Barsukova, Anna (2011)
The participation of mitochondria in cellular and neuronal Ca(2+) homeostatic networks is now well accepted. Yet, critical tests of specific mitochondrial pathways in neuronal Ca(2+) responses have been hampered because the identity of mitochondrial proteins that must be integrated within this dynamic system remain uncertain. One putative pathway for Ca(2+) efflux from mitochondria exists through the formation of the permeability transition pore (PTP) that is often associated with cellular and neuronal death. Here, we have evaluated neuronal Ca(2+) dynamics and the PTP in single adult neurons in wild-type mice and those missing cyclophilin D (CyPD), a key regulator of the PTP. Using high-resolution time-lapse imaging, we demonstrate that PTP opening only follows simultaneous activation with two physiological stimuli that generate critical threshold levels of cytosolic and mitochondrial Ca(2+). Our results are the first to demonstrate CyPD-dependent PTP opening in normal neuronal Ca(2+) homeostatic mechanisms not leading to activation of cell death pathways. As neurons in mice lacking CyPD are protected in a number of neurodegenerative disease models, the results suggest that improved viability of CyPD-knockout animals in these pathological states may be due to the transient, rather than persistent, activation of the PTP in mutant mitochondria, thereby shielding neurons from cytoplasmic Ca(2+) overload.